DETERMINAN PENDAPATAN PEDAGANG KULINER DI PANTAI JEMPOL KABUPATEN SUMBAWA - Nining Sudiyarti; S Suprianto; Novi Kadewi Sumbawati; Virda Dwi Nopianti (Pusat Riset dan Publikasi, 2020)
Traders' income can be affected by many factors. In this study using two factors, namely capital and the number of work hours. This study aims to know the influence of the capital factor and the number of work hours toward the income of culinary traders in Jempol Beach, Sumbawa district. The type of research used in this study was associative with quantitative data. The data in this study was primary that have obtained through structured interviews. This study was conducted at Jempol Beach, Sumbawa district, with a population of 30 traders. The sample in this study were 30 respondents who were taken through saturated sampling technique (census). The variables used include capital (X1), number of hours worked (X2), and income (Y). The data analysis used was multiple linear regression (OLS) with a significance level of 5%.The results of study showed that partially the variable of capital (X1) had a significant effect toward the income of culinary traders in Jempol Beach, Sumbawa district, while the variable of number of working hours (X2) had no significant effect toward the income of culinary traders in Jempol Beach, Sumbawa district. Furthermore, the variables of capital and the number of working hours together have a significant effect toward the income of culinary traders in Jempol Beach, Sumbawa Regency, the influence of it was 61.6% while the remaining was 38.4% (100% -61.6%) was explained by other variables.